Prediction of major clinical response (ACR50) to infliximab in psoriatic arthritis refractory to methotrexate. Issue 4 (19th December 2006) - Gratacós, J; Casado, E; Real, J; Torre-Alonso, J C
Abstract : Objectives: To determine the predictive factors of clinical response to infliximab in patients with refractory psoriatic polyarthritis. Methods: A multicentre open study which included 69 patients with psoriatic polyarthritis refractory to methotrexate (15 mg/week at least for 8 weeks). Patients were treated with infliximab 5 mg/kg every 8 weeks in addition to their stable doses of methotrexate. A major clinical response was defined by the ACR50 at week 38. Logistic regression analysis was performed to analyse which of the following measures at the start of treatment were associated with an ACR50 response: demographic and clinical characteristics, duration of disease, tender and swollen joint counts, involvement of large joints (knee or hip, or both), erythrocyte sedimentation rate, C reactive protein (CRP), Health Assessment Questionnaire disability index, axial involvement, and the presence of erosions at baseline. Results: In an intention to treat analysis 30/69 (44%) patients achieved an ACR50 response. In the univariate analysis both the presence of large joint involvement and severe disability were associated with a poor clinical response. In a multivariate logistic regression analysis high CRP values were independently associated with a good therapeutic response (odds ratio (OR) = 18.7; 95% confidence interval (CI) 1.8 to 181.6; p = 0.011). In contrast, large joint involvement and severe disability were associated with a poor response, which reached significance for large joint involvement (OR = 29.3; 95% CI 3.2 to 266.3; p = 0.003). Conclusion: A lower disability and, in particular, the absence of large joint involvement and higher CRP serum levels at the start of infliximab treatment are factors that seem to influence the probability of achieving a good therapeutic response in patients with psoriatic arthritis.